(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Corruption has been the object of study in much research, but only recently have begun to investigate it experimentally. One way to study this phenomenon is to expose the participants in a Public Goods Game (PGG) in which they need to contribute to producing a particular public good, and then need to make decisions about how this good will be distributed among all the participants. A participant who makes distributions unequally for his own benefit shall behave in a manner analogous to that described in the crime of peculation. The aim of this study was to investigate how the participants distributed public resources in the PGG. Six participants were exposed to the procedure. Five participants made unequal distributions, i.e., they allocated most of the resources to themselves. From these results, we suggest changes in the contingencies that control the occurrence of this type of behaviour.